(untitled) (Jurnal Edukasi dan Penelitian Matematika, 2025)
The ability to solve problem is one of the crucial skills in mathematics education that is important for logical and analytical thinking in students. However, currently, problem solving among 11th grade students at SMAN 1 Padang Ganting is still low. This reseach aims to evaluate whether students who are taught using Team-Assisted Individualization (TAI) model perform better than those who follow the direct instruction model. The study combines descriptive research and a simple experiment using the “Non-equivalent Posttest Only Control Group Design.” The study population consists of eleventh-grade students at SMAN 1 Padang Ganting for the 2024/2025 academic year. The sample was selected using simple random sampling. XI F2 was chosen as the experimental class, while XI F4 was designated as the control class. The measurement tools were quizzes and final tests that assessed mathematical problem-solving skills. The research indicates that the average quiz scores increased with each meeting. Furthermore, hypothesis testing of the final test results yielded a P-value < α = 0.05, indicating that the students’ ability to solve mathematical problems in the experimental class was better than the students in the control class. Therefore, the TAI model to have a positive impact on improving mathematical problem-solving skills.